2020
DOI: 10.2298/psi190704019s
|View full text |Cite
|
Sign up to set email alerts
|

Effects of unpleasant odors on emotion recognition: The right hemisphere and valence-specific hypotheses

Abstract: The right hemisphere has traditionally been considered as dominant in odor and emotion perception, whereas little is known about odor influence on emotion recognition. This study aimed to examine a possible difference in the recognition of basic emotions presented to the left or the right visual field following short-term left or right nostril treatment with an unpleasant odor. A total of 60 right-handed female participants completed an emotion recognition task in conditions of the right and left nostril treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Pictures of faces were presented in the left or right visual fields while participants were exposed to an unpleasant odor in the left or right nostril. Participants were faster at recognizing faces overall in the left visual field (right hemisphere) during exposure to the odor in the right nostril (right hemisphere), indicating a cross-modal confluence in the right hemisphere resulted in a processing speed advantage; however, the study had no neutral control condition, so it is possible that the arousing effect of the odor, irrespective of its valence, improved processing of faces in the stimulated hemisphere (Stankovic et al, 2020). The right-hemisphere effect is consistent with results from our team that the face-sensitive N170 ERP component is more prominent in the right hemisphere; furthermore, our study showed that the responsivity of the N170 to disgusted faces is enhanced by an unpleasant odor (Syrj€ anen et al, 2018).…”
Section: Odor Effects On the Processing Of Face Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…Pictures of faces were presented in the left or right visual fields while participants were exposed to an unpleasant odor in the left or right nostril. Participants were faster at recognizing faces overall in the left visual field (right hemisphere) during exposure to the odor in the right nostril (right hemisphere), indicating a cross-modal confluence in the right hemisphere resulted in a processing speed advantage; however, the study had no neutral control condition, so it is possible that the arousing effect of the odor, irrespective of its valence, improved processing of faces in the stimulated hemisphere (Stankovic et al, 2020). The right-hemisphere effect is consistent with results from our team that the face-sensitive N170 ERP component is more prominent in the right hemisphere; furthermore, our study showed that the responsivity of the N170 to disgusted faces is enhanced by an unpleasant odor (Syrj€ anen et al, 2018).…”
Section: Odor Effects On the Processing Of Face Stimulimentioning
confidence: 99%
“…Some studies have also presented stimuli in the left and right visual fields. In Stankovic et al (2020), participants performed an emotion classification task on neutral or happy, surprised, fearful, angry, disgusted, and sad facial expressions. Pictures of faces were presented in the left or right visual fields while participants were exposed to an unpleasant odor in the left or right nostril.…”
Section: Odor Effects On the Processing Of Face Stimulimentioning
confidence: 99%
“…Pictures of faces were presented in the left or right visual fields while participants were exposed to an unpleasant odor in the left or right nostril. Participants were faster at recognizing faces overall in the left visual field (right hemisphere) during exposure to the odor in the right nostril (right hemisphere), indicating a cross-modal confluence in the right hemisphere resulted in a processing speed advantage; however, the study had no neutral control condition, so it is possible that the arousing effect of the odor, irrespective of its valence, improved processing of faces in the stimulated hemisphere (Stankovic et al, 2020). The right-hemisphere effect is consistent with results from our team that the face-sensitive N170 ERP component is more prominent in the right hemisphere; furthermore, our study showed that the responsivity of the N170 to disgusted faces is enhanced by an unpleasant odor (Syrjänen et al, 2018).…”
Section: Odor Effects On the Processing Of Face Stimulimentioning
confidence: 99%
“…Some studies have also presented stimuli in the left and right visual fields. In (Stankovic, Nesic, & Milic, 2020), participants performed an emotion classification task on neutral or happy, surprised, fearful, angry, disgusted, and sad facial expressions.…”
Section: Odor Effects On the Processing Of Face Stimulimentioning
confidence: 99%
“…So, for example, Leppänen and Hietanen reported that their participants were able to recognize disgusted facial expressions more rapidly in an unpleasant odour context while happy expressions were recognized more rapidly in a pleasant odour context instead. The presence of pleasant versus unpleasant odours have also been shown to result in the enhanced recognition of both disgusted and happy facial expressions (Seubert et al, 2010b ; see also Li et al, 2020 ; Stankovic et al, 2020 , who presented isovaleric acid). Using functional MRI, Seubert et al ( 2010a ) were able to demonstrate that the processing of disgusted faces was facilitated by the prior presentation of odour primes.…”
Section: The Influence Of Odour On Person Perceptionmentioning
confidence: 99%